PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI DUNKIN DONUTS JALAN SAM RATULANGI KOTA MANADO - Yessy Br. Sembiring; Leonardus Ricky Rengkung; Agnes Estephina Loho (AGRI-SOSIOEKONOMI, 2019)
The objective of this research in to determine the affect of marketing mix of consumer purchasing decisions at Dunkin Donuts, Sam Ratulangi Street, Manado City. This data collection was conducted in two days on Desember 17, 2018 and April 01, 2019. The data used are primary and secondary data. Primary data is obtained from direct interviews with consumers of DunkinDonuts. While secondary data was obtained from books available at local bookstores and the internet such through google scholar to access articles from various scientific journals and theses from other universities related to the topic of this research, especially concerning to the influence of the marketing mix. The number of respondents 60 sample. It was taken by using simple random sampling. Data analysis method is a logistic regression model because the dependent variable model in the model is a categorical variable, giving a value of 1 to consumers who decide to buy and thevalue of 0 consumers who decide not to buy. The research result showed that there were two marketing mix variables that had a significant effect, namely product (X1) and price (X2) while the variables that did not have a significant effect on consumer purchasing decisions at Dunkin Donutsnamely place (X3) and promotion (X4).*jnkd+eprm*